“I just went into it assuming that I wouldn’t be able to have the full experience”: Understanding the Accessibility of Virtual Reality for People with Limited Mobility - Mott, Martez; Tang, John; Kane, Shaun; Cutrell, Ed; Morris, Meredith Ringel (ASSETS 2020, 2020)
Virtual reality (VR) has the potential to transform many aspects of our daily lives, including work, entertainment, communication, and education. However, there has been little research into understanding the usability of VR for people with mobility limitations. In this paper, we present the results of an exploration to understand the accessibility of VR for people with limited mobility. We conducted semi-structured interviews with 16 people with limited mobility about their thoughts on, and experiences with, VR systems. We identified 7 barriers related to the physical accessibility of VR devices that people with limited mobility might encounter, ranging from the initial setup of a VR system to keeping VR controllers in view of cameras embedded in VR headsets. We also elicited potential improvements to VR systems that would address some accessibility concerns. Based on our findings, we discuss the importance of considering the abilities of people with limited mobility when designing VR systems, as the abilities of many participants did not match the assumptions embedded in the design of current VR systems.